Old age in the family. Care of a senior as a challenge for the adult child or for the state? - Błachnio, Aleksandra (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2016)
Approaches to ageing changes because of the significant increase in the number of the elderly. On the national scale, ageing is connected with alarming forecasts about financial inefficiency in the health and social welfare sectors; on the family scale it proves the increasing deficits in long-term care provision caused by the crisis of ties, and the financial migration of the young. Thus the author presents the necessary revision of the understanding of old age, as well as argues for a more active involvement of the elderly in society and the family.
Keywords: ageing; family; state; grandmother; grandfather; University of Third Age; Informational Communication Technology (ICT)